2004
DOI: 10.1016/j.jpaa.2004.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Strongly torsion free, copure flat and Matlis reflexive modules

Abstract: In this paper we show that if R is a ring of Krull dimension d and M is a strongly copure at (respectively, strongly copure injective) module, then E ⊗R M (respectively, HomR(E; M )) is strongly cotorsion (respectively, strongly torsion free) for any injective module E. We obtain a new characterization for copure at modules. We prove that M is copure at if and only if Ext 1 R (M; F) = 0 for all at cotorsion modules F. Moreover, if (R; m) is a Cohen-Macaulay local ring and M is strongly copure at, then HomR(M; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Многие свойства этих модулей были описаны в работах Енохса, Дженды, Сазиди, Динга и Мао, и т.д. [1]- [6]. В статье [2] кочистые инъективные и кочистые плоские модули сыграли важную роль в характеризации -мерных колец Горенштейна (т.е.…”
Section: математические заметкиunclassified
“…Многие свойства этих модулей были описаны в работах Енохса, Дженды, Сазиди, Динга и Мао, и т.д. [1]- [6]. В статье [2] кочистые инъективные и кочистые плоские модули сыграли важную роль в характеризации -мерных колец Горенштейна (т.е.…”
Section: математические заметкиunclassified
“…Recall that a left R-module M (resp., right R-module N ) is called strongly cotorsion (resp., strongly torsionfree) [23,18] if Ext 1 (F, M) = 0 (resp., Tor 1 (N , F) = 0) for any left R-module F with f d(F) < ∞.…”
Section: Left Noetherian Rings With Id( R R) ≤ Nmentioning
confidence: 99%
“…A right R-module F is said to be copure flat [11] if Tor 1 (F, N ) = 0 for all injective left R-modules N , and F is said to be strongly copure flat [11] or weakly Gorenstein flat [13] if Tor i (F, N ) = 0 for all injective left R-modules N and all i ≥ 1. Copure injective modules and copure flat modules were discovered when studying injective precovers and flat preenvelopes and have been studied by many authors (see [7,10,11,18]). …”
Section: Introductionmentioning
confidence: 99%
“…Sazeedeh [6] showed that an R-module M satisfies Tor Proof. To prove the necessity part, let N be any R-module and assume M satisfies…”
Section: Proof Consider a Presentation 0 →mentioning
confidence: 99%